Analysis of allergic diseases incidence against the background of priority health problems in the group of children and adolescents of the Łęczyński Poviat - Bednarek, Anna; Emeryk, Andrzej; Dońka, Katarzyna (Polish Journal of Public Health, 2012)
Introduction. The health status of children and adolescents conditioned by the influence of endogenic determinants and ecological and cultural modifiers often favors the development of many health problems in children and adolescents, including the increasing incidence of allergic diseases in developed countries. Aim. Assessment of the prevalence of allergic diseases against the background of the priority health problems of the school community in Łęczna Poviat. Material and methods. There were analyzed 1450 cards of preventive health examination of primary school, secondary school and high school students of Łęczna Poviat in 2007 and 2008, regards the prevalence of allergic diseases and priority health problems. Results. The most common health problems of students in the examined schools are locomotor system defects (48.6%), ocular defects: students in grades IV-VI – 26.2%, gymnasium – 24.0% and 25.3% of secondary school-, followed by short stature evident in the largest percentage of students in grades IV-VI, and overweight dominant in classes IV-VI (8.5%) and secondary school (7.9%). In primary school in the classes I-III, and IV-VI there were allergic diseases to a similar extent (6.0% and 6.2%), and the highest percentage among them was asthma (2.4% and 3.8%). Conclusions. In the classification of priority health problems of school children allergic diseases similarly occupied the third and fifth place after the defects of musculoskeletal system and vision, overweight and obesity. In all types of schools (primary, gymnasium and high school), gender significantly differentiates the incidence of allergic diseases and other health problems. Knowledge of the health situation of students outlines priorities for health promotion in the population of school children, as well as health education on prevention of allergic diseases.